2021
DOI: 10.1111/gcb.15865
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation composition modulates the interaction of climate warming and elevated nitrogen deposition on nitrous oxide flux in a boreal peatland

Abstract: Nitrous oxide (N 2 O) is a potent greenhouse gas that contributes 6% to global warming (IPCC, 2013) and can cause ozone destruction in the stratosphere (Ravishankara et al., 2009). Northern peatlands have accumulated not only large stocks of organic carbon (C) but also a great amount of organic nitrogen (N), approaching 415 Pg C and 10 Pg N (Hugelius et al., 2020). Despite this large organic N storage, peatlands are nutrient-poor ecosystems because organic N is not like mineral N that can be absorbed by vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…In the typical steppe, N 2 O emission increased with the increases of plant aboveground biomass. Such a positive relationship was also found in previous studies, especially under N addition (Gong & Wu, 2021; Zhang et al., 2014). Nitrogen addition weakened the competition for N‐nutrient between plants and microorganisms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the typical steppe, N 2 O emission increased with the increases of plant aboveground biomass. Such a positive relationship was also found in previous studies, especially under N addition (Gong & Wu, 2021; Zhang et al., 2014). Nitrogen addition weakened the competition for N‐nutrient between plants and microorganisms.…”
Section: Discussionsupporting
confidence: 87%
“…A study in a restored peatland showed that nitrate uptake by Eriophorum vaginatum controlled N 2 O emission (Silvan et al., 2005). Nowadays, the plant effect on N 2 O emission was mainly focused on peatlands (Brummell et al., 2017; Gong & Wu, 2021). It is an increasing need to explore the effect of plants on soil N 2 O emission in uplands under the scenario of increasing precipitation and N deposition.…”
Section: Introductionmentioning
confidence: 99%
“…LULC changes may lead to the destruction of vegetation, resulting in changes in NDVI, and LULC may cause changes in microclimate, which in turn affects NDVI [80]. Factors other than land-use and temperature, precipitation, downgradient shortwave radiation, and CO 2 are ignored in our study, but nitrogen deposition [81], topography [82], and forest fires [83] can also affect changes in vegetation. The temporal and spatial precision of the land-use data in our study is not high enough.…”
Section: Discussionmentioning
confidence: 98%
“…Data available from the Figshare: https://doi.org/10.6084/m9.figshare.22634356.v2 (Gong et al., 2023).…”
Section: Data Availability Statementmentioning
confidence: 99%